2001
DOI: 10.1002/1521-3765(20011119)7:22<4954::aid-chem4954>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Difference between the Manganese Porphyrin and Corrole Analogues of Cytochrome P450's Compound I?

Abstract: Density functional calculations on oxo-manganese complexes of corrole (1) and porphyrin (2 and 3) show a fundamental difference. The ground state of I is the singlet manganese(V) state, 1A(MnV), in which corrole is a closed shell. In contrast, 2 and 3 have high-spin manganese(IV) states, 1A1u and 3A2u respectively. This difference and the state ordering for each system are rationalized based on the competition between the intrinsic tendency of manganese to prefer high-spin electronic configurations, vis-à-vis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(30 citation statements)
references
References 37 publications
4
23
0
Order By: Relevance
“…In unpublished work (Ghosh A, Dey A, unpublished results) we have found that B3LYP calculations with comparable basis sets favor the diamagnetic Mn(V) state by a smaller margin of about 0.3 eV. In contrast, Gross, Shaik and co-workers [39] [40]. B3LYP calculations on Mn(corrolato)(O) predicts a closed-shell Mn(V) state as the ground state-a qualitatively correct result-but the Mn(IV)-oxo corrole p-cation radical states lie barely about 0.1-0.2 eV higher in energy [36].…”
Section: Discussionmentioning
confidence: 88%
“…In unpublished work (Ghosh A, Dey A, unpublished results) we have found that B3LYP calculations with comparable basis sets favor the diamagnetic Mn(V) state by a smaller margin of about 0.3 eV. In contrast, Gross, Shaik and co-workers [39] [40]. B3LYP calculations on Mn(corrolato)(O) predicts a closed-shell Mn(V) state as the ground state-a qualitatively correct result-but the Mn(IV)-oxo corrole p-cation radical states lie barely about 0.1-0.2 eV higher in energy [36].…”
Section: Discussionmentioning
confidence: 88%
“…The chemistry of porphyrin-metal-oxo [10], corrole-metal-oxo [7,[11][12][13][14][15], and corrolazine-metaloxo species [16,17] have received considerable attention. Iron(IV)-oxo porphyrin radical cation models of Compound I have been known for more than two decades [18], and they have been characterized by various spectroscopic methods, such as UV-vis, EPR, Mö ssbauer, EXAFS and Raman spectroscopies [19].…”
Section: Introductionmentioning
confidence: 99%
“…4 We also averaged the error of the GGAþU and GGA splittings for each intermediate with respect to the CCSD(T) splittings for that intermediate. The average error for the five spin splittings along the reaction coordinate is 0.04 eV in GGAþU, to be compared with GGA, which exhibits an average error of 0.20 eV, or B3LYP that performs even more poorly with an average error of 0.30 eV in the splittings.…”
Section: Resultsmentioning
confidence: 99%
“…In biological systems, mid-row 3d transition metals facilitate reactions as diverse as methane-to-methanol conversion at an antiferromagnetically coupled dimetal center [1,2], unactivated alkane halogenation by a highenergy, high-spin ferryl-oxo center in the halogenase SyrB2 [3], and oxygen binding at iron porphyrins in hemoglobin [4]. In inorganic catalysts, many transition metal complexes have been designed to carry out synthetic pathways that mimic active biological catalytic cycles.…”
Section: Introductionmentioning
confidence: 99%